The acoustic properties, syllable structure, and syllable sequences of ultrasonic vocalizations (USVs) during neonatal opioid withdrawal in FVB/N mouse substrains - Kelly K. Wingfield; Teodora Misic; Sophia A. Miracle; Carly S. McDermott; Kaahini Jain; Nalia M. Abney; Kayla T. Richardson; Mia B. Rubman; Jacob A. Beierle; Elisha M. Wachman; Camron D. Bryant (Addiction Neuroscience, 2025)
Concomitant with the opioid epidemic, there has been a rise in pregnant women diagnosed with opioid use disorder and infants born with neonatal opioid withdrawal syndrome (NOWS). NOWS refers to withdrawal signs following cessation of prenatal opioid exposure that comprise neurological, gastrointestinal, and autonomic system dysfunction. A critical indicator of NOWS severity is excessive, high-pitched crying.However, NOWS evaluation is mostly subjective, and additional cry features may not be easily recognized during clinical assessment. Thus, there is a need for more objective measures of NOWS severity. We used a third trimester-approximate opioid exposure paradigm to model NOWS traits in genetically similar inbred substrains of FVB/N mice (NJ, NCrl, NHsd, and NTac). Pups were injected twice daily from postnatal day 1 (P1) to P14 with morphine (10 mg/kg, s.c.) or saline (20 microliters/g, s.c.).Because there were very few minor substrain differences in spontaneous withdrawalinduced ultrasonic vocalization (USV) profiles, we collapsed across substrains to evaluate the effects of morphine withdrawal on additional USV properties. We identified syllable sequences unique to morphine-withdrawn and saline-control FVB/N pups on P7 and P14. We also observed an effect of spontaneous morphine withdrawal on the acoustic properties of USVs on P7 and P14. Some withdrawal traits correlated with acoustic properties of USVs in morphine-withdrawn FVB/N pups on P7 and P14. This in-depth investigation of mouse USV features during spontaneous neonatal opioid withdrawal has implications for predicting neonatal opioid withdrawal severity in mice and applying objective approaches to understanding cries in human infants suffering from NOWS.